2017
DOI: 10.3892/mmr.2017.8123
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol induces autophagy and apoptosis of osteosarcoma through PI3K/Akt/mTOR signaling pathway

Abstract: Honokiol is the main active constituent of Magnolia officinalis. With effective and long‑term pharmacological functions of being antibacterial, anti‑oxidative, anti‑inflammatory, antitumor, anti‑spasmic, anti‑anxiety and anti‑viral, Honokiol is clinically used in the treatment of acute enteritis and chronic gastritis. The aim of the present study was to observe the possible anti‑effects of honokiol on autophagy and apoptosis of osteosarcoma, and to investigate the role of the PI3K/Akt/mTOR signaling pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
(29 reference statements)
2
29
0
Order By: Relevance
“…Other studies have also shown that honokiol induces autophagy in PC-3 and LNCaP prostate cancer cells via the suppression of mTOR and Akt phosphorylation [77]. Another study revealed that the treatment of neuroblastoma cells with honokiol caused significant downregulation of mTOR phosphorylation, which leads to the induction of autophagy of neuroblastoma cells (neuro-2a cells) through the PI3K/Akt/mTOR signalling pathways [96,195].…”
Section: Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 94%
“…Other studies have also shown that honokiol induces autophagy in PC-3 and LNCaP prostate cancer cells via the suppression of mTOR and Akt phosphorylation [77]. Another study revealed that the treatment of neuroblastoma cells with honokiol caused significant downregulation of mTOR phosphorylation, which leads to the induction of autophagy of neuroblastoma cells (neuro-2a cells) through the PI3K/Akt/mTOR signalling pathways [96,195].…”
Section: Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 94%
“…Recent studies showed that SIRT3 exhibits mighty deacetylase activity and is the key regulator in organ protection under many pathologic states including inflammatory and oxidative stress, acting pivotal roles in development and progression of metabolic diseases including diabetes, neurodegenerative disorders, and other diseases . Honokiol (HNK), [2‐(4‐hydroxy‐3‐prop‐2‐enyl‐phenyl)‐4‐prop‐2‐enyl‐phenol], is a bioactive compound obtained from Magnolia grandiflora which possesses multiple properties including anti‐tumor, anti‐arrhythmic, anti‐thrombocytic, anti‐inflammatory, anti‐angiogenesis, anxiolytic, anti‐oxidative activities in vivo and in vitro . As a potent reactive oxygen species (ROS) scavenger, it is also reported that HNK can enhance the overexpression of SIRT3 to improve antioxidant activity and mitochondrial energy regulation thereby reducing the levels of Aβ and sAPPβ in Chinese Hamster Ovarian (CHO) cells .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Honokiol (HNK), [2-(4- anti-oxidative activities in vivo and in vitro. [16][17][18][19][20][21] As a potent reactive oxygen species (ROS) scavenger, it is also reported that HNK can enhance the overexpression of SIRT3 to improve antioxidant activity and mitochondrial energy regulation thereby reducing the levels of Aβ and sAPPβ in Chinese Hamster Ovarian (CHO) cells. 22 Additionally, Xian et al suggested that HNK could improve learning and memory impairments induced by scopolamine in mice and attenuate the concentration of prostaglandin E2 and cyclooxygenase-2 level and the neuroinflammatory processes.…”
mentioning
confidence: 99%
“…Among the various compounds, pterostilbene (PTE), which is a methylated resveratrol derived from plants, has been shown to inhibit CSC properties in breast cancer [67,68], glioma [69], hepatocellular carcinoma [70], and lung cancer [71] through the inhibition of multiple pathways which are possibly related to the CSC propagation such as Wnt, Hedgehog, Notch, and PI3K/Akt. Honokiol (HNK), which is the extract from Magnolia obovata, has shown its various antitumor effects through the inhibition of several pathways such as PI3K/Akt/mTOR, Wnt, and c-Myc [72][73][74]. Besides these effects of PTE and HNK, we have identified that PTE in combination with HNK could be the possible metabolism-targeted therapy against osteosarcoma as a "two hit" or "dual inhibition" of metabolic pathways, OXPHOS and glycolysis.…”
Section: Novel Approach To Target Cellular Metabolism In Osteosarcomamentioning
confidence: 99%